Urine and stool pH values in malnutrition - Özsoylu, Şinasi; Şenol, Necla (The Turkish Journal of Pediatrics, 1967)
Urine and stool pH values were determined in 58 and 68 calorie malnutrition cases respectively and compared with control cases. The stool and urine pH values did not seem to be related to the degree of malnutrition. Acquired lactase deficiency which might occur in malnutrition cases could not always be shown with stool pH values.